PENERAPAN MOTIVASI BERPRESTASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Sandi Bega (Sekolah Tinggi Teologi Duta Panisal, 2020)
Motivation is very much needed in learning, without motivation, students cannot participate in learning well. Therefore, it is a must for students to have motivation in learning. Students who have motivation in learning can exert energy within themselves to follow and complete the learning well and can direct themselves to achieve the objectives of the learning. With the existence of motivation owned by students in learning, it will automatically form achievement motivation where students act to do and complete the learning task correctly as an attempt to achieve success or succeed in competition with a measure of excellence in the form of achievement. In learning Christian Religious Education, achievement motivation is needed to encourage, direct and realize Christian values. With the achievement motivation, making Christian Religious Education learning not only limited to subject matter but used as a referencein building the foundation of faith in God, the character and personality development of students themselves.